Insights from Cognitive and Ritual Studies: A Response to Kaler’s and Tite’s Papers on Religious Experience in Nag Hammadi and Gnosticism - Uro, Risto (Bulletin for the study of religion, 2013)
Since the 1990s, scholarly debates and discussions in Gnostic or Nag Hammadi studies have largely revolved around the issues of whether the category of "Gnosticism" is helpful or detrimental in the analysis of ancient texts and how to classify the texts that were traditionally labeled "gnostic" as well as the groups that produced them. The debate about the category of "Gnosticism" in particular has brought up important issues concerning the ideological commitments of the scholars working on the Nag Hammadi texts and helped to analyze the identity formation process that shaped the history of the variety of early Christian groups during the first three centuries, but the debate has also somewhat exhausted itself. There is certainly room for new approaches and research questions. The panel on religious experience organized by the SBL Nag Hammadi and Gnosticism section and the two papers by Michael Kaler and Philip Tite presented in the panel and published in BSOR can be seen as welcome moves towards something new. Both papers share an interest in what might be called religious experience studies and therefore engage themselves in cross-disciplinary theoretical reflection and cross-fertilization between recent trends in religious studies and gnostic studies. This paper provides a critical response to these two papers with a particular emphasis on ritual and cognitive studies.